Nutrient Requirement of Saladette Tomato Harvested in two Clusters - Alejo-Santiago, Gelacio; Rivas-Mencias, Omar A.; Aburto-González, Circe-Aidín; Juárez-Rosete, Cecilia Rocío; Sánchez-Monteón, Ana Luisa (REVISTA TERRA LATINOAMERICANA, 2024)
Saladette tomato is the most consumed vegetable in the world, but excessive fertilization practices generate environmental pollution. Using the balanced nutrition method is an advantage to calculate fertilization doses that allows specified quantities based on waiting yield goals. In addition to soil supply and fertilizer recovery ef ficiency, nutritional value is required, which considers the need for nutrients to produce aerial and underground plant biomass. In the case of saladette tomato - a crop that can be managed intensively with one stem and only two floral clusters - the nutritional requirement value was lacking with this management. Therefore, the objective of this study is to generate the nutritional value of tomato plants established under greenhouse and fertigation conditions. At 70 days af ter transplanting, Ten plants were extracted at 70 days af ter transplanting to quantify fresh and dry weight; commercial and non-commercial fruit production were quantified, as well as each plant organ. Subsequently, nitrogen (N), phosphorus (P) and potassium (K) concentrations from each organ were analyzed and the amount of nutrients necessary to achieve a ton of commercial fruit was calculated in this type of management. The results indicate that commercial fruit production per plant was 1.0 kg; the organ that accumulates the least dry matter is the root. The nutritional requirement expressed in kg per ton of fresh fruit is: N 0.78, P 0.12, and K 1.74.